Differences in Adverse Childhood Experiences and Coercive Control among Native American and Non-Native American Justice-Involved Women. Issue 1 (2nd January 2023) - Jones, Melissa S.; Worthen, Meredith G. F.; Heim, Mackenzie; Sharp, Susan F.; McLeod, David A.
ABSTRACT: The purposes of the current study are two-fold. First, we examine how ACEs influence being a victim of IPV coercive control among Native American ( n = 92) and non-Native American ( n = 263) justice-involved women using data from the 2014 Oklahoma Study of Mother's and Their Children. Second, because little research exists on these relationships, we explore how these patterns may vary among Native American and non-Native American women. Our findings suggest that there is not only a clear link between ACEs and coercive control among justice-involved women, but also that these relationships vary between Native American and non-Native American women.